Services, Quality of Life And Satisfaction of Senior Citizens in Bacolod City (International Journal of Scientific Research and Management (IJSRM), 2023)
The main purpose of this study was to come up with a general description and relationship among the extent of services, quality of life and satisfaction of senior citizens in Bacolod city. The areas of services include; health social access to public transport, utility discount and mandatory Philhealth coverage. Areas in the quality of life includes; health status, financial security, organizational affiliation, household relations and access to senior citizens’ benefits. Areas on satisfaction includes; appreciation of good health, social support, emotional security, contentment and leisure and activity. The study employed the descriptive, comparative and relational analytical schemes in coming up with a general description, comparison and relationship among the selected variables. The mean, t-test and Pearson Product Moment of Correlation formula was used. Findings of the duty revealed that senior citizens were adequately provided with all these services particularly on health, social public transport, utility discount and mandatory Philhealth services. They are experiencing quality living with regards ti their relationship in their household and access to Philhealth benefits. However, findings showed that they are not adequately contented with regards to health condition and financial security. They were having high level of satisfaction on the aspect of social support, emotional security, and leisure activities. Moreover, study showed that there was significant relationship between services and quality of life of senior citizens. Likewise, a significant relationship between the services and satisfaction of senior citizens and a significant relationship between the satisfaction and quality of life of senior citizens has existed. The study concluded that on services, although the extent was not at its highest degree of contentment to the services but senior citizens were contented of all the services provided to them. On quality of life, senior citizens were not fully contented and happy about the quality of life they were experiencing to note that a moderate extent on contentment was perceived by the senior citizens. On satisfaction, senior citizens degree of satisfaction was high considering that majority of life satisfaction was perceived by them to be high particularly in social, emotional, leisure and contentment. It was concluded further that senior citizens were not fully satisfied or contented about their health condition. The study highly recommends that medical programs/project shall provide greater emphasis on the following; married, low income, rural areas, male, without college degree senior citizens. Social services programs/project shall provide greater emphasis on the following; married, low income, rural areas, without college degree. Access to public transport programs/project shall provide greater emphasis on the following; married, low income. Utility discount programs/project shall provide greater emphasis on the following; married, without college degree, low income and leisure activity with greater emphasis on married, without college degree and low income senior citizens